PENERAPAN KEDAULATAN RAKYAT DI DALAM PEMILIHAN UMUM DI INDONESIA BERDASARKAN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Ofis Rikardo (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2020)
ABSTRACTElections are a means of implementing the sovereignty of the people regulated in the 1945 Constitution. In the implementation of indirect democracy, a representative democratic system is inevitable, so that elections that uphold direct, public, free, secret, honest and fair spirit are a means of regenerating leadership politics to run the government both at central and regional levels. People as the owner of the highest sovereignty surrender their sovereignty to state institutions such as the President, DPR, DPD, and DPRD through elections. After the change in the 1945 Constitution there was a shift in the regulation of popular sovereignty such as the MPR is no longer the executor of popular sovereignty, the implementation of direct presidential elections by the people, until the emergence of the Constitutional Court that can try and decide the president and vice president to stop in his term of office. All of this is an effort to uphold the people's sovereignty and at the same time to maintain the people's sovereignty based on the 1945 Constitution. Keywords: People's Sovereignty, Elections, 1945 Constitution